Influences of Frozen Ground and Climate Change on Hydrological Processes in an Alpine Watershed: A Case Study in the Upstream Area of the Hei'he River, Northwest China. (15th November 2016) - Zhang, Yanlin; Cheng, Guodong; Li, Xin; Jin, Huijun; Yang, Dawen; Flerchinger, Gerald N.; Chang, Xiaoli; Bense, Victor F.; Han, Xujun; Liang, Ji
Abstract: In cold regions, the occurrence of frozen ground has a fundamental control over the character of the water cycle. To investigate the impact of changing ground temperature conditions on hydrological processes in the context of climate change, a distributed hydrological model with an explicit frozen ground module was applied to an alpine watershed in the upstream area of the Hei'he River in the Qilian Mountains, northwest China. After evaluating the base model, we considered scenarios of frost‐free ground and climate change. Results showed that the base model with a frozen ground module successfully captured the water balance and thermal regimes in the basin. When the frozen ground module was turned off, the simulated groundwater recharge and base flow increased by a factor of two to three because surface runoff caused by exceeding infiltration capacities at high elevations, which occurred in the base model, was eliminated. Consequently, the river hydrograph became smoother and flatter, with summer flood peaks delayed and reduced in volume. The annual mean depth where subsurface runoff was generated, was about 2.4 m compared to 1.1 m in the base model. For a warming climate, a combination of increasing evapotranspiration and reducing permafrost area results in smoother and flatter hydrographs, and a reduction in total river discharge. Although our analysis using numerical models has its limitations, it still provides new quantitative understanding of the influences of frozen ground and climate change on hydrological processes in an alpine watershed. Copyright © 2016 John Wiley & Sons, Ltd.